2006
DOI: 10.1258/135763306778558132
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of 46 static telecytology cases over a period of two years

Abstract: We analysed 46 telecytology cases sent from two rural hospitals about 500 km from a tertiary cancer centre. The cases were submitted for second opinion over a period of two years and evaluated using a static store and forward telecytology approach. A total of 715 digital images were studied (average 15 per case). Forty-one of the 46 cases (89%) were reported within 3 days and 54% of cases were reported within one working day. The aspiration smears and images were found to be of diagnosable quality in 89 and 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…[2][3][4][5][6] We sometimes faced the criticism that cytotechnologist might not always pick (sample) the cells showing the most important abnormal feature in telecytology diagnosis. In addition, we have also heard people say that it was impossible to adequately express three-dimensional structure of cell cluster as a single still image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] We sometimes faced the criticism that cytotechnologist might not always pick (sample) the cells showing the most important abnormal feature in telecytology diagnosis. In addition, we have also heard people say that it was impossible to adequately express three-dimensional structure of cell cluster as a single still image.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] In each country or community, there might be various factors influencing the penetration of telecytology. However, we have often heard that one of the reasons is that a static image system only provides limited information to the consulting cytopathologist.…”
mentioning
confidence: 99%
“…SDI platforms capture, store, and forward galleries of digital images for remote assessment. SDI-based telecytology proved to be popular [22,23,24], with advantages including relatively low equipment start-up costs, minimal equipment maintenance, and smaller image files that are easier to manage and store. However, telecytology using SDI suffers from an inability to focus, lack of resolution, and dependency on the referring host to preselect clinically relevant ROI to be photographed [25,26].…”
Section: Emerging Applications In Digital Technologymentioning
confidence: 99%
“…This hypothesis speaks to the fact that image selection quality and bias may play an important role in the variable quality of static-image telecytology. For a variety of aspiration specimens, Jialdasani et al [32] reported a ‘clinically useful’ diagnosis in 91% of cases using static-image telecytology. Yamashiro et al [33] report on their introduction of a static image-based telecytology system for primary diagnosis in Japan.…”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%